If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2+6=8-4x/6
We move all terms to the left:
2+6-(8-4x/6)=0
We add all the numbers together, and all the variables
-(-4x/6+8)+2+6=0
We add all the numbers together, and all the variables
-(-4x/6+8)+8=0
We get rid of parentheses
4x/6-8+8=0
We multiply all the terms by the denominator
4x-8*6+8*6=0
We add all the numbers together, and all the variables
4x=0
x=0/4
x=0
| 8x-6(3-x)=10 | | 162=-2x+4(3x+13) | | 1/2(x+3)=1/3(3x+6) | | 4-3p=16 | | t²-9+18=0 | | 15x+(-3)=-11+13x | | 4-3p=14 | | 1=1/4x+5+3 | | 162=-2x+4(3x+13 | | 7(v+2)-3v=2(2v+3)-9 | | t*2-9+18=0 | | 20=y=8 | | 3=q2 | | 0=-16t+8t+24 | | 57=15+6y | | -4x+2(5x+2)=52 | | 0.7x+4=340 | | 12x(2)=6(20) | | W=3x15/8 | | 24+2x=3x+2(12) | | 12^2x+3=144 | | 4b=10b–84 | | -28=5u+7 | | 7t+27=5t+47 | | 36-8x=7x+2 | | 6y=5y+12 | | 98=6x+4(3x+2) | | 2s=s+71 | | 75+x+42=180 | | 5w=w+44 | | 3x-14=5x+44 | | 16-(m+1)=2(2m-1) |